Kepemimpinan: Suatu Tinjauan Manajemen Sumber Daya Manusia - Januar Heryanto (Bina Nusantara University, 2005)
Leadership qualities might naturally “inborn” to some people, but for some others have to make efforts to grow the leadership qualities in themselves. It’s wellknown as a “formed-leaders”, leadership that grows through examples and experiences. Leaders should have a vision to see the future from the distance. They dream is not only about what can be happened to day, but also about what will happen in next year, in next decade, even in next generation.